An Interview with Mr. Kul Man Ghising - Ghising, Kul Man (Hydro Nepal: Journal of Water, Energy and Environment, 2017)
In light of ongoing discourses, at present, on prevailing energy crisis and its management as well as the hydropower development in Nepal, HYDRO Nepal Journal felt this timely to review and assess the present energy scenario of Nepal. HYDRO Nepal takes pleasure in presenting an interview with Mr. Kul Man Ghising, Managing Director, Nepal Electricity Authority, with Mr. Upendra Dev Bhatta, Editor-in-Chief of HYDRO Nepal Journal. HYDRO Nepal Journal Journal of Water Energy and Environment Issue: 20 Page: 60-64